Anxiety trajectories: An observational study of women undergoing chemotherapy for breast or gynecological cancer. (December 2022) - Suskin, Johanna A.; Paul, Steven; Stuckey, Ashley R.; Conley, Yvette P.; Hammer, Marilyn J.; Miaskowski, Christine; Dunn, Laura B.
Abstract: Background: While anxiety is prevalent among women who undergo chemotherapy for breast or gynecologic cancer, research on its predictors has focused primarily on cross-sectional evaluations or on assessments of anxiety prior to and after receipt of chemotherapy. Few studies have evaluated for predictors of inter-individual variability in levels of anxiety during chemotherapy. This study evaluated for inter-individual differences in anxiety across two cycles of chemotherapy and identified demographic, clinical, symptom, and psychological adjustment (e.g., stress, coping) characteristics associated with initial levels and trajectories of anxiety. Methods: Patients with breast (n = 530) or gynecologic (n = 233) cancer completed the Spielberger State Anxiety Inventory six times over two cycles of chemotherapy. At enrollment, self-report measures were used to assess demographic, symptom, stress, and coping characteristics. Hierarchical linear modeling was used to evaluate for risk factors associated with initial levels and trajectories of state anxiety. Results: At enrollment, demographic, clinical, symptom, and psychological adjustment characteristics associated with inter-individual differences of anxiety were: marital status, functional status, sleep disturbance, cognitive function, global stress, cancer-specific stress, resilience, sense of coherence, and the coping strategies of venting and self-blame. Employment status and morning fatigue were the only characteristics associated with inter-individual differences in the trajectories of anxiety. Denial was the only characteristic associated with both initial levels and the trajectories of anxiety. Conclusions: A variety of patient characteristics predicted initial levels of anxiety. Fewer characteristics predicted trajectories of anxiety. Identification of specific risk factors, such as avoidant coping, suggests the need for targeted interventions among higher-risk patients. Highlights: Anxiety impacts women receiving chemotherapy for breast and gynecological cancer. Few studies explore inter-individual differences in anxiety in this population. We studied demographic, clinical, symptom, and psychological characteristics. Such factors are associated with anxiety levels and can inform future interventions.